2012
DOI: 10.5539/ies.v6n2p33
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Services Quality of Palestine Higher Education

Abstract: The history of the Palestinian universities is relatively recent; however their impact on the Palestinians case and wellbeing is undeniable. Today, almost forty years later the Palestinian universities like many higher education institutions in the region and worldwide tussle to fulfil the students’ demands on education while trying to maintain high quality and relevant education. In Palestine; studies of higher education sector seems to focus primarily on easily quantifiable indicators such as teacher vs. stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 55 publications
4
18
0
1
Order By: Relevance
“…This finding supports those of Jusoh et al (2004), Tan and Kek (2004), Koni et al (2013) and Wilkins and Balakrishnan (2013), which were all conducted in developing nations. They are, however, contradictory to the findings of Joseph et al (2005), Min and Khoon (2014), Palli and Mamilla (2012), and Zafiropoulos and Vrana (2008), two of which were conducted in developed nations.…”
Section: Gendersupporting
confidence: 91%
See 1 more Smart Citation
“…This finding supports those of Jusoh et al (2004), Tan and Kek (2004), Koni et al (2013) and Wilkins and Balakrishnan (2013), which were all conducted in developing nations. They are, however, contradictory to the findings of Joseph et al (2005), Min and Khoon (2014), Palli and Mamilla (2012), and Zafiropoulos and Vrana (2008), two of which were conducted in developed nations.…”
Section: Gendersupporting
confidence: 91%
“…This finding supports the finding of Min and Khoon (2014) and Palli and Mamilla (2012) but disagrees with Koni et al (2013). Since our study covered a relatively constrained age grouping (mostly 18 to 23 years old), such similarity of opinions is not unexpected.…”
Section: Agesupporting
confidence: 90%
“…SERVQUAL comprises five dimensions namely-tangibles, reliability, responsiveness, assurance and empathy. This evaluation method was utilized as some researchers recommended to be used in higher education institutions (e.g., Seymour, 1992;Arambewela & Hall, 2006;Dado et al, 2012;Ibrahim et al, 2013;Ilyasi et al, 2013;Koni et al, 2013).…”
Section: Service Quality Evaluation Methodsmentioning
confidence: 99%
“…On the other hand, age has some influence on behavior intentions (e.g., Salanova et al, 2005;Realo & Dobewall 2011;Koni et al, 2013). This applies to study level, as a significant relationship was reported with behavior intentions where students tend to make the decision to transfer to other institutions normally during the first and second year of study (Koni et al, 2013).…”
Section: Perceived Services Quality and Behavior Intentionsmentioning
confidence: 99%
“…However, most of the literature on students' perceived service quality is still, to our knowledge, based on developed countries, such as Australia (Soutar and McNeil, 1996;Sultan and Wong, 2012), Japan (Sultan and Tarafder, 2007;Sultan and Wong, 2010), Spain (Calvo-Porral et al, 2013;Gallifa and Batalle, 2010), UK (Russell, 2005), and USA (Joseph et al, 2005). Little attention has been paid for such studies in developing countries, such as India (Senthilkumar and Arulraj, 2011), Indonesia (Sumaedi et al, 2012), and Malaysia (Abdulla, 2006), with very limited studies targeting higher education in Arab countries such as Lebanon (Abouchedid and Nasser, 2002), State of Palestine (Koni et al, 2013), and the United Arab Emirates (Badri et al, 2004). This triggers the need for more investigations of students' perceived service quality in the context of higher education in developing, especially Arab, countries.…”
Section: Introductionmentioning
confidence: 99%